Unhappily non-cooperative: Do development research and practice ignore each other? - Linda Kleemann; Maximilian Neumann (Kiel Institute for the World Economy (IfW), 2014)
Successful cooperation between development researchers and development policy makers and practitioners translates into better development policies, projects and programmes. Research is relevant if it can provide meaningful input for the practitioners. At the same time, practitioners have to be willing and able to use these findings to improve their work. Through continuous communication, evaluation and feedback cycles both parties should be able to gain additional insights and improve future outcomes. But how close is reality to this ideal state of collaboration between theory and practice? Development researchers are often said to be working in ivory towers - doing research for the sake of publications with results that are hardly relevant or applicable in practice. But is this necessarily so and is it the only reason for the lack of cooperation between research and practice? What role do personal communication, time horizons and the researchers' fear of losing their academic reputation play? To answer this question, we developed two surveys, one among development researchers and one among development practitioners in Germany, asking them about the intensity and quality of cooperation and feedback linkages between research and practice. We also asked about the main obstacles and the expectations about the future of cooperation between the two groups. The questionnaires were published on the PEGNet website and contained 27 questions. The researcher questionnaire was sent to about 2000 development researchers in Germany and abroad in early 2014. Within three weeks 145 researchers answered the questionnaire. The practitioner questionnaire was distributed in 2013 (Kleemann and Böhme 2013). Although the results are not representative for the development research sector as a whole they provide some interesting insights into existing problems and what can be done about them. The results show that both researchers and practitioners are interested in cooperating more. Researchers in particular believe that better collaboration would be mutually beneficial, resulting in additional insights for their research and better development outcomes. From their point of view the current state of cooperation is unsatisfactory because of four main reasons: different interests, different time frames, poor communication and mistrust. The practitioners' and researchers' opinion on the main obstacles for cooperation coincide to a large extent, and in particular on the question of timing. Practitioners complain about the slowness of research wherefore they have to make decisions before the researchers can provide them with their findings (Bell and Squire 2014). Moreover, practitioners claim that researchers are mainly aiming at publishing their results and are therefore neglecting the applicability of their research. Hence, in order to improve the cooperation environment researchers and practitioners have to learn how to trust and respect each other, to communicate better and to find ways to handle differences in timing.
Keywords: 330